Tissue‐resident and memory properties of human T‐cell and NK‐cell subsets. Issue 8 (12th August 2016) - Lugli, Enrico; Hudspeth, Kelly; Roberto, Alessandra; Mavilio, Domenico
Abstract : T‐cell and NK‐cell subsets recirculate through blood, lymph and secondary lymphoid organs and peripheral tissues. Additional subsets of these cells are stably resident in specific tissues and do not recirculate. In the case of T cells, resident cells have also memory properties, are thus called tissue‐resident memory T (TRM ) cells and provide a first line of defense against invading pathogens. Also NK cells show resident (such as in the human liver) and adaptive, memory‐like traits, although these aspects do not necessarily overlap. Abstract : Efficient immune responses to invading pathogens are the result of the complex but coordinated synergy between a variety of cell types from both the innate and adaptive arms of the immune system. While adaptive and innate immune responses are highly complementary, some cells types within these two systems perform similar functions, underscoring the need for redundancy and increased flexibility. In this review, we will discuss the striking shared features of immunological memory and tissue residency recently discovered between T cells, a component of the adaptive immune system, and natural killer (NK) cells, members generally assigned to the innate compartment. Specifically, we will focus on the T‐cell and NK‐cell diversity at the single‐cell level, on the discrete function of specific subsets, and on their anatomical location. Finally, we will discuss the implication of such diversity in the generation of long‐term memory.